(4Z)-1-[(E)-(4-Methoxybenzylidene)amino]-2-phenyl-4-[(thiophen-2-yl)methylidene]-1H-imidazol-5(4H)-one - Vikram D. Singh; Kamni; K. N. Subbulakshmi; B. Narayana; B. K. Sarojini; Sumati Anthal; Rajni Kant (IUCrData, 2016)
In the title compound, C22H17N3O2S, the imidazole ring forms dihedral angles of 9.2 (2), 10.9 (2) and 12.5 (2)° with the thiophene, phenyl and methoxy-substituted benzene rings, respectively. There are two intramolecular C—H...N hydrogen bonds forming S(5) and S(6) rings and one intramolecular C—H...O hydrogen bond forming an S(6) ring.